Trehalosemodulates OVRAS to improve oxidative stress and apoptosis in KGN cells and ovaries of PCOS mice - Shasha Gao; Juan Wang; Lun Wei; Chao Luo; Fei Qian; Le Bo; Caiping Mao (Journal of Ovarian Research, 2024)
Abstract The etiology of polycystic ovary syndrome (PCOS) is complex and variable, and there is no exact cause or good treatment method. Most of the methods of hormones are used to temporarily meet the needs of patients. Experimental evidence has shown that trehalose has, anti-apoptotic, anti-oxidative, glucose-lowering, and insulin resistance effects. However, whether trehalose has a therapeutic effect on PCOS is unknown. It has been reported that the ovarian renin-angiotensin system (OVRAS) is involved in the development of PCOS, but it has not been fully elucidated. This study aims to explore the effect of trehalose on PCOS and elucidate the related OVRAS mechanism. We first observed that body weight, estrous cycle, ovarian follicles at all levels, glucose tolerance, serum hormones, and insulin resistance were improved by trehalose treatment in the PCOS mouse model. Moreover, trehalose treatment also ameliorated ovarian oxidative stress and apoptosis in PCOS mice, as determined by TUNNEL apoptosis staining, total SOD in ovarian homogenate, and WB assay. OVRAS mainly involves two classic pathways, namely the ACE/AngII/AT1R/AT2R, and ACE2 / Ang1-7/ MASR, Which play different functions. In PCOS mouse ovaries, we found that ACE/AngII/AT1R was up-regulated and ACE2/Ang1-7/MASR and AT2R were down-regulated by PCR and WB experiments, However, trehalose treatment changed its direction. In addition, we also found that trehalose ameliorated DHEA-induced oxidative stress and apoptosis in KGN by PCR and WB experiments, mainly by down-regulating ACE/AngII/AT1R. Our study shows that trehalose improves symptoms of PCOS mainly by down-regulating ACE/AngII/AT1R, revealing a potential therapeutic target for PCOS.